The diversity of endophytic fungi associated with Piper nigrum in the tropical areas: A recent study from Kutai Kartanegara, Indonesia - SOPIALENA SOPIALENA; SUYADI SUYADI; MUHAMAD SAHIL; JULI NURDIANA (Society for Indonesian Biodiversity, 2018)
Sopialena, Suyadi, Sahil M, Nurdiana J. 2018. The diversity of endophytic fungi associated with Piper nigrum in the tropical areas: a recent study from Kutai Kartanegara, Indonesia. Biodiversitas 19: 2028-2034. This research aimed to identify the diversity of endophytes fungal in the root and leaves of Piper nigrum Linn. This research contributes to the knowledge gaps by focusing the discussion on the Endophytic fungal communities of Piper nigrum Linn in tropical areas at Kutai Kartanegara, Indonesia. Two certain plots within the study area were selected based on the different characteristics of topographic contours. The locations, named Plot A was characterized by ramps area, while plot B was sloping or hilly area. A total of 55 isolates were obtained from the root and the leaves of healthy plants, 35 isolates were from Plot A and the other 20 isolates were from plot B. Based on Shannon index (H’), both of the plots corresponded to the same genus; namely Aspergillus sp., Fusarium sp., Nigrospora sp., and Trichoderma sp, and categorized as medium diversity. In this regards, this study confirms that the genus Aspergillus sp. and Fusarium sp. represent a large part of the diversity of Endophytes fungi. As the study indicates that plot B has higher diversity of endophytic fungi compared to plot A, it shows that the hilly area turns out to be a better location for Piper nigrum Linn.